Inequality and the Tails: the Palma Proposition and Ratio. Issue 1 (February 2016) - Cobham, Alex; Schlögl, Lukas; Sumner, Andy
Abstract: The Palma Proposition is that changes in income or consumption inequality are (almost) exclusively due to changes in the share of the richest 10 per cent and poorest 40 per cent because the 'middle' group between the richest and poorest tend do capture approximately 50 per cent of gross national income (GNI). The Palma Ratio is a measure of income or consumption concentration based on the above‐mentioned proposition and calculated as the GNI capture of the richest 10 per cent divided by that of the poorest 40 per cent. In this paper we revisit the empirical basis of the Palma Proposition (the relative stability of the 'middle') with a new and expanded data set across and within developing and developed countries. We find the data reaffirms the Palma Proposition and that the proposition is getting stronger over time. Abstract : Palma Ratio also helps to focus the policy debate on inequality on what can be done effectively.